Tourism Potentiality and Infrastructure Planning with Special Reference to the Dehing-Patkai Region: An Analysis - Bordoloi, Anjan Kumar (Prabandhan: Indian Journal of Management, 2012)
This article presents the importance of Tourism in the present context. It also focuses on the Dehing Patkai region as a highly potential place for tourism in the economies of the North Eastern (NE) Region in India. This article does not seek to propose a comprehensive job-creation strategy through tourism, but to outline steps necessary to reinforce the potential role that tourism can play in general and in job creation, in particular, and points out the policy steps that can be taken in this direction.